Pengaruh Pemberian Pakan Komplit Berbasis Silase Campuran Sorghum dan Daun Gamal Pada Level yang Berbeda Terhadap Kadar Kolestrol Darah Trigliserida dan Hemoglobin Ternak Kambing Lokal Betina - Maukaling, Yosua; Sobang, Yohanes U.L.; Amalo, Daud; Maranatha, Grace (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this study was to determine the effect of giving complete feed based on silage mixed with sorghum and gamal leaves at different levels on blood cholesterol, triglyceride and hemoglobin levels in female local goats. In this study, 4 female local goats aged 6-8 months were used with a body weight range of 11-15 kg with an average of 12.88 kg and a coefficient of variation of 6.74%. The experimental method used the Latin Square Design (RBSL) with 4 treatments and 4 periods as repetition consisting of P0 = 80% silage + 20% concentrate, P1 = 70% silage + 30% concentrate, P2 = 60% silage + 40% concentrate , P3 = 50% silage + 50% concentrate. Parameters observed were blood cholesterol, triglyceride and hemoglobin levels of livestock. The results of this study indicated that the effect of complete feeding based on silage mixed with sorghum and gamal leaves at different levels on blood cholesterol, triglyceride and hemoglobin levels of female local goats had no significant effect (P>0.05) on blood cholesterol, blood triglyceride levels, blood hemoglobin levels of local female goats. The conclusion from the complete feeding based on silage mixed with sorghum and gamal leaves at different levels has no significant effect on blood cholesterol, triglyceride and hemoglobin levels.